2008
DOI: 10.1007/s10577-008-1241-7
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy for imaging human metaphase chromosomes

Abstract: The present study introduces the principle of atomic force microscopy (AFM) and reviews our results of human metaphase chromosomes obtained by AFM. AFM imaging of the chromosomes revealed that the chromatid arm was not uniform in structure but had ridges and grooves along its length, which was most prominent in the late metaphase. The arrangement of these ridges and grooves was roughly symmetrical with the counterpart of the paired sister chromatids. AFM imaging of banded chromosomes also showed that the ridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Before the AFM imaging of chromosomes, it was necessary to select suitable spreads of metaphase 2002; Hoshi et al, 2007b;Ushiki et al, 2008). In the present study, we succeeded in obtaining AFM images and fluorescent images of topoisomerase II in the same chromosome, and showed that the distribution of topoisomerase II was denser in the ridged regions than in the grooved regions.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Before the AFM imaging of chromosomes, it was necessary to select suitable spreads of metaphase 2002; Hoshi et al, 2007b;Ushiki et al, 2008). In the present study, we succeeded in obtaining AFM images and fluorescent images of topoisomerase II in the same chromosome, and showed that the distribution of topoisomerase II was denser in the ridged regions than in the grooved regions.…”
Section: Resultsmentioning
confidence: 61%
“…However, the specimens should be fixed, dried and metal coated for this purpose, procedures often induce preparation artifacts on the the structure of specimens to be studied. As a means of overcoming these limitations, we have been investigating in atomic force microscopy (AFM) to clarify the higher-order structure of the chromosomes, especially in a liquid environment (Ushiki and Hoshi, 2008). These studies revealed that the chromatid arm of the human metaphase chromosome has ridges and grooves along its length and that these ridges and grooves roughly correspond to the G/Q-positive and G/Q-negative bands, respectively (Ushiki et al, 2002;Hoshi et al, 2007;Ushiki et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…3). The highest chromosome features were observed (400-800 nm) by AFM on native chromosome preparations Ushiki and Hoshi, 2008]. Our focus was to investigate the topography on chromosomes routinely prepared for molecular cytogenetic analysis, and heat or enzymatic treatment is unavoidable.…”
Section: Discussionmentioning
confidence: 99%
“…Compatible AFM and FISH protocols were developed to simultaneously determine topography and investigate whether α-satellite DNA and a component protein marker co-localize on these structures. AFM generates topographic information at nanometer scale resolution ( ∼ 30 nm), overcoming some limitations of optical microscopy [Thalhammer et al, 2004;Ushiki and Hoshi, 2008]. The method routinely prepares cytogenetic specimens without additional chromosomal pretreatments required for scanning (SEM) or transmission electron microscopy [Liu et al, 2003].…”
mentioning
confidence: 99%
“…The following protocol was developed for different cell lines such as HeLa cells (Hoshi et al, 2004;Ushiki & Hoshi, 2008).…”
Section: Chromosome Preparationmentioning
confidence: 99%